OP0171 Leptin levels, overweight and p gingivalis presence contribute to the mechanism of systemic inflammation in first-degree relatives of rheumatoid arthritis individuals. (12th June 2018) - Romero-Sanchez, C; Chaparro-Sanabria, J.A.; Bello-Gualtero, J.M.; Valle-Oñate, R.; Chila, L.; Castillo, D.M.; Lafaurie, G.; Chalem Ch, P.; Bautista-Molano, W.
Abstract : Background: Association studies in rheumatoid arthritis (RA) have been focused in the pre-clinical phases of the disease in first-degree relatives (FDR). Data has shown that obesity, ACPA and the periodontal condition may modulate the severity and the clinical presentation of RA Objectives: To investigate the levels of adipokines in FDR and establish their association with the state of rheumatic and periodontal condition Methods: 124 FDR individuals and 124 healthy controls matched by age and gender were included. Rheumatologic (clinical and serological markers) and periodontal assessment was performed. It was quantified the adiponectin, leptin, IL6 levels. HLA-DRB1 was determined. Serum markers of RA (rheumatoid factor, erythrocyte sedimentation rate, C reactive protein (CRP), and APCA. P gingivalis and IgG1/IgG2 P gingivalis were measured. Radiographs of hands and feet were evaluated the Sharp-van der Heijde score. An association analysis was made to evaluate the relationship between adipokines and periodontal, rheumatologic conditions using X2 test, and logistic regression model was performed to confirm this associations Results: In FDR group, 71.77% were women with a mean age of 39.24±12.22 years. 37.09% had overweight and 4.83% had obesity. Among the controls, 70.97% were women, with an average age of 39.31±12.30 years. 27.41% had overweight and 4.83% had obesity. Leptin levels were found in 37.66% vs 18.42% in controls(p=0.002). In FDR, 60.48% had periodontal disease of which 62.66% moderate, P gingivalis in 62.10%. In controls, 55.64% had periodontal disease, of which 63.76% moderate with 42.74% P gingivalis positive (p=0.002). In the FDR, radiography of hands and feet showed in 25.28% of them had some alteration, 68.18% had ≥1 erosion, 45.45% had ≥1 joint space narrowing and in 6.89% juxtaarticular osteopenia. An association of leptin levels with the low economic level was found p=0.006 and high levels of leptin in individuals with BMI ≥30 p=0.031. IL6 was found to be associated with severity of periodontal disease, with higher levels being found frequently in mild periodontal disease p=0.039.The condition of FDR was significantly associated with high leptin levels adjusted for presence of swollen joints, presence of P gingivalis and low levels of IL6 OR=2, 57, 95% CI: 1.14 to 5.95. In this group, the individual with leptin at moderate levels adjusted with BMI >25, has a lower probability of presenting CRP >3 mg/L OR=0.43 95% CI: 0.20 to 0.90. Conclusions: High levels of leptin, the presence of P gingivalis and swollen joints may be relevant conditions associated with the development of RA in FDR.Leptin levels and overweight can modulate the production of acute phase proteins in this group of individuals contributing to the mechanism of systemic inflammation. The clinical implications of our findings propose regulated exercise programs, oral hygiene, and weight control in FDR Reference: [1] Unriza-Puin S, et al. Clin Rheumatol2017;28(36):799–806. Disclosure of Interest: None declared